Income Analysis of Chili Pepper Farming - Wantoro, Bambang Hadi; Jumiati, Jumiati; Akbar, Akbar (JURNAL AGRIBISAINS, 2024)
The purpose of this study is to analyze the cost of cayenne pepper cultivation in Balassuka village, Tombolo Pao district, Gowa regency, to analyze the production and income of chili pepper cultivation in Balassuka village, Tombolo Pao district, Gowa regency, and to analyze the economic viability of chilli cultivation. In Balassuka Village, Tombolo Pao District, Gowa Regency. A random sample of 31 respondents was used in this study. The informants were cayenne pepper growers. The data collection techniques used were interviews and observation and analysis through qualitative analysis and quantitative analysis. The results of the study show that the cultivation of cayenne pepper in Balassuka Village, Tombolo Pao District, Gowa Regency is feasible in the forecast period. The income from cayenne pepper cultivation in Balassuka Village, Tombolo Pao District, Gowa Regency averages IDR 7,640,204,600 per hectare per season and the profit is IDR. Rs. 7 126 501 850. These results show a positive value, so it can be said that the farmer’s income level is quite high.